Cyberculture and Sustainable Development: Communicative, Ethical and Technological Transformations - Hurova, Inna; Shapovalov, Heorhii; Ishchuk, Alla; Morklyanyk, Bohdan; Balanyuk, Yuriy; Temnikov, Volodymyr; Hnatovska, Нanna; Kalyta, Olena (European Journal of Sustainable Development, 2025)
Contemporary urban agglomerations confront the intertwined challenges of population growth, resource constraints, environmental degradation, and the imperative to enhance quality of life. In response, digital transformation – driven by information technologies (IT), the Internet of Things (IoT), and the virtualization of social and technological processes – has given rise to the “smart city” paradigm. This article employs a systems-thinking approach to examine how cyberculture influences not only the technical optimization of urban services but also the evolving values and communication practices that support participatory governance and collective responsibility. Drawing on case studies, we show that the convergence of AI, IoT, and big-data analytics generates synergies for energy management, mobility, waste and water governance, and green infrastructure. These developments reflect a shift toward ecological responsibility, dematerialization, and digital inclusion, while reshaping language norms and creating platforms for more open civic dialogue and deliberation. We also discuss critical perspectives on the calculative logic underlying smart-city systems and highlight emerging modes of collaborative innovation and knowledge sharing. We conclude that cyberculture, both as a driver of value formation and a medium of communicative innovation, serves as a key enabler of sustainable development, with ongoing implications for justice, resilience, and well-being for current and future generations. Keywords: cyberculture, smart city, sustainable development, value transformation, communication practices, digital ethics, collective intelligence, participatory governance, language norms